2012
DOI: 10.1016/j.febslet.2012.07.003
|View full text |Cite
|
Sign up to set email alerts
|

The function of the NADPH thioredoxin reductase C‐2‐Cys peroxiredoxin system in plastid redox regulation and signalling

Abstract: a b s t r a c tProtein disulphide-dithiol interchange is a universal mechanism of redox regulation in which thioredoxins (Trxs) play an essential role. In heterotrophic organisms, and non-photosynthetic plant organs, NADPH provides the required reducing power in a reaction catalysed by NADPH-dependent thioredoxin reductase (NTR). It has been considered that chloroplasts constitute an exception because reducing equivalents for redox regulation in this organelle is provided by ferredoxin (Fd) reduced by the phot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
50
0
2

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 61 publications
(53 citation statements)
references
References 60 publications
1
50
0
2
Order By: Relevance
“…A key component of the rapid adjustment of chloroplast metabolism to ever-fluctuating light conditions is the redox regulation of enzyme activity, which relies on two thiol redox systems, the NADPHdependent NTRC and the Fdx-dependent FTR/Trx pathways (Spínola et al, 2008;Cejudo et al, 2012). Thus, a central issue in understanding chloroplast redox regulation is to establish the functional relationship between these two redox systems and the relevance of chloroplast redox regulation to plant development.…”
Section: Discussion Ntrc Acts In Concert With Different Types Of Trxsmentioning
confidence: 99%
“…A key component of the rapid adjustment of chloroplast metabolism to ever-fluctuating light conditions is the redox regulation of enzyme activity, which relies on two thiol redox systems, the NADPHdependent NTRC and the Fdx-dependent FTR/Trx pathways (Spínola et al, 2008;Cejudo et al, 2012). Thus, a central issue in understanding chloroplast redox regulation is to establish the functional relationship between these two redox systems and the relevance of chloroplast redox regulation to plant development.…”
Section: Discussion Ntrc Acts In Concert With Different Types Of Trxsmentioning
confidence: 99%
“…Plants and some algae possess an additional NTR enzyme, called NTRC, which contains a small-type NTR domain at the N-terminus and a Trx domain at the C-terminus (Serrato et al 2004). Previous studies demonstrated that NTRs play an essential role in various biological processes such as stress tolerance, development, and metabolism including the biosynthesis of starch and chlorophyll (Cha et al 2014;Reichheld et al 2007;Cejudo et al 2012).…”
Section: The Thioredoxin Superfamily Proteinsmentioning
confidence: 99%
“…12 Compared to typical NTRA and NTRB, NTRC has been largely identified from biochemical reactions to physiological functions in Arabidopsis. 13 Loss-of function NTRC mutant in Arabidopsis showed obvious pale-green leaves and dwarf phenotypes due to defects of chloroplast biogenesis and auxin levels, respectively.…”
Section: Stress Defense Mechanisms Of Nadph-dependent Thioredoxin Redmentioning
confidence: 99%
“…Furthermore, electrons from NADPH produced in chloroplast transfer to 2Cys Prx via redox-active cysteins in TrxR and Trx domain in NTRC. 13,16,17 However, cytosolic NTRA and mitochondrial NTRB are acquired to cooperate with their relevant Trx counterparts. NTRA and NTRB also share redundant function in cytosol and mitochondria both in vitro and in vivo.…”
Section: Stress Defense Mechanisms Of Nadph-dependent Thioredoxin Redmentioning
confidence: 99%